Effects of infrastructure on the adoption of sustainable agricultural practices in sub-Saharan Africa - Abdul-Hanan Abdallah (Circular Agricultural Systems)
Adopting sustainable agricultural practices (SAPs) is critical for achieving circular agricultural systems (CAS) in sub-Saharan Africa, as these practices emphasize resource efficiency, waste reduction, and sustainable management of natural resources. Infrastructure, including irrigation and produce/product storage facilities, play a vital role in enabling the effective implementation of SAPs by improving resource use efficiency, reducing post-harvest losses, and supporting the recycling and reuse of agricultural inputs—key principles of CAS. However, investment in infrastructure by African governments remains low, raising concerns about its role in driving the adoption of SAPs and the necessary transformations for sustainable agricultural development. Using a panel dataset from sub-Saharan Africa and advanced econometric techniques—including a correlated random effect with a multivariate probit (CRE-MVP), a control function approach (CRE-CFA), and an ordered probit with endogenous treatment (CRE-OPRETRE) models—this study accounts for potential interrelationships between SAPs and endogeneity due to observed and unobserved heterogeneity. The analysis examines the effects of irrigation and produce/product storage infrastructure on the adoption and extent of adoption of SAPs. The results reveal that, in addition to influencing the decision to adopt SAPs, each type of infrastructure significantly increases the proportion of households adopting SAPs at higher levels. These findings underscore the importance of investing in production and post-production infrastructure to promote SAPs, aligning with CAS principles by fostering sustainable resource use, enhancing resilience, and minimizing environmental impact.